+0  
 
0
110
1
avatar

1. Simplify Each of the following:

a. the sum of 6x + 2 and -8x + 5

b. the result of subtracting 5x - 17 from 8x + 12

c. the product of 7x and 4x - 9

 

2. Solve 2/3 (3x + 14) = 7x + 6, by the first multiplying both sides of the equation by 3, before applying the distributive property.

 

Thanks!

Guest Apr 15, 2017
Sort: 

1+0 Answers

 #1
avatar+75333 
+2

1.

a.

 6x + 2 - 8x + 5   =

6x - 8x + 2 + 5  =

-2x  + 7

 

b.

{8x + 12 ] -  [5x - 17 ] =

8x  - 5x  + 12  - (-17)  =

3x + 29

 

c.  (7x) (x - 9)  =  7x * 4x  - 7x * 9    =   28x^2  - 63x

 

2.

2/3 (3x + 14) = 7x + 6     multiply through by 3

2(3x + 14)  = 21x + 18    simplify

6x + 28  =  21x + 18       subtract 6x, 18 from both sides

10 = 15x                         divide both sides by 15 and reduce the fraction

10/15  = x  = 2/3

 

 

cool cool cool

CPhill  Apr 15, 2017

6 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details